Sorption and diffusion studies of radiocesium in soil samples from Ibu Kota Nusantara region of Indonesia - Hana Fikrinabilah Dely Supratman; Hendra Adhi Pratama; Budi Setiawan; Mochamad Adhiraga Pratama; Sucipta Sucipta; Sitti Hijraini Nur; Nurul Efri Ekaningrum; Gustri Nurliati; Moh. Cecep Cepi Hikmat; Andry Setiawan; Niken Siwi Pamungkas; Zico Pratama Putra; et al. (Environmental Chemistry and Ecotoxicology)
A plan by Indonesia to develop a Nuclear Power Plant (NPP) 1750 km from the new capital city, Ibu Kota Nusantara (IKN), has increased the need for radiocesium (radio-Cs) sorption and diffusion studies to reduce environmental concerns during reactor operation and decommissioning. This study provides the first comprehensive assessment of the physical, chemical, and mineral aspects of three soil samples (HA, M, and E) from the IKN region to figure out how these characteristics affect the mobilization of radio-Cs in the soil. To achieve this, radio-Cs apparent diffusion (Da) and distribution (Kd) coefficients were determined for each soil sample. Mineralogical revealed distinct characteristics among the samples, with the E sample having the highest clay content of 46.18 %, followed by HA (36.27 %) and M (23.69 %). The Da in groundwater (GW) solvent achieved at 12 × 10−12 m2/s for HA, 5.80 × 10−12 m2/s for M, and 9.91 × 10−12 m2/s for E sample. In Deionized water (DW) solvent, the Da obtained at 2.57 × 10−12 m2/s for HA, 3.10 × 10−12 m2/s for M, and 2.79 × 10−12 m2/s for E sample. The lower diffusion rates (Da) in DW compared to GW suggest reduced competition from other cations, limiting cesium ion interaction. The Kd values in GW were valued at 1949.82 mL/g, 1864.60 mL/g, and 3450.83 mL/g, for HA, M, and E samples, respectively. Meanwhile, the Kd values in DW increased up to 2262.73 mL/g, 2106.14 mL/g, and 3819.23 mL/g for HA, M, and E samples, respectively. The E sample offered the largest distribution coefficient (Kd) across all solvents, highlighting the significant impact of clay concentration on adsorption capacity. These findings highlight the significant impact of soil features in determining the behavior of radio-Cs, which has important implications for strategies related to environmental monitoring and remediation mitigation in IKN region.